PENGARUH UKURAN PERUSAHAAN, RETURN ON EQUITY, RETURN ON INVESTMENT, NET PROFIT MARGIN TERHADAP HARGA SAHAM - Syifa Rizqiyyah; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This research aims to test the effect of company size, return on equity, return on investment and net profit margin on stock prices. Company size, return on equity, return on investment and net profit margin as independent variables. Stock prices are a dependent variable. This study used secondary data with a population of 44 companies, namely nickel sub-sector mining companies listed on the Indonesia Stock Exchange in 2021-2024, as many as 36 companies were samples of research with the 2021-2024 observation year. The sampling technique used is purposive sampling by multiple linear regression analysis methods. The results of this study show that the size of the company and Return On Equity have no effect on stock prices. Meanwhile, Return On Investment and Net Profit Margin have an impact on stock prices.